Occurrence of aflatoxin B1 in conventional and organic flour in Italy and the role of sampling. (April 2015) - Armorini, Sara; Altafini, Alberto; Zaghini, Anna; Roncada, Paola
Abstract: Aflatoxins (AFs) are mycotoxins produced by certain species of Aspergillus and aflatoxin B1 (AFB1) is the most toxic, consistently carcinogenic and genotoxic. In the present study, a total of 90 different samples of organic and conventional flours (20 conventional wheat flour, 20 organic wheat flour, 42 conventional corn flour, and 8 organic corn flour) were analyzed for the presence of AFB1. The samples were purchased from local stores in the surrounding of Bologna during the period April to May 2013. For the quantification of AFB1 in flours, a fast and sensitive HPLC–FD method was developed and tested for several validation parameters (linearity and range, specificity, accuracy and precision, LOD, LOQ and recovery). AFB1 was found in 13 samples of corn flour, specifically 4 organic and 9 conventional. These results confirm a higher incidence of contamination in corn compared to wheat, as reported in literature. No significant differences were observed in the concentration of AFB1 by comparing conventional corn flour samples and organic corn flour samples ( P  > 0.05). The levels of contamination found in the positive samples ranged between 0.17 and 3.75 μg kg −1 but only in one case the limit defined at Community level (2 μg kg −1 ) was exceeded. This demonstrates the effectiveness of the network of monitoring before the placing on the market of these food products. Furthermore, in this study efforts were made to evaluate the minimum quantity of flour related to a commercial package, which is reliable for the assessment of contamination by AFB1. In fact, in sample preparation, the selection of the sample size for the laboratory analysis is a very important step. The minimum amount to get a reliable result is 20 g and smaller quantities can lead to incorrect results. Highlights: We studied the occurrence of aflatoxin B1 (AFB1) in organic and conventional flours. No significant differences in AFB1 contamination in the two categories of product. Except in one case, the levels of AFB1 contamination never exceed the law limit. The choice of the test sample size for laboratory analysis is a very important step. For AFB1, the minimum amount of flour sample to get a reliable result is 20 g.